186 because you would divide 341 by 11 and you get 31 then multiply that by 6 and you get 186. Did this help?
Answer:
√(p²-4q)
Step-by-step explanation:
Using the Quadratic Formula, we can say that
x = ( -p ± √(p²-4(1)(q))) / 2(1) with the 1 representing the coefficient of x². Simplifying, we get
x = ( -p ± √(p²-4q)) / 2
The roots of the function are therefore at
x = ( -p + √(p²-4q)) / 2 and x = ( -p - √(p²-4q)) / 2. The difference of the roots is thus
( -p + √(p²-4q)) / 2 - ( ( -p - √(p²-4q)) / 2)
= 0 + 2 √(p²-4q)/2
= √(p²-4q)
Answer: How can I help?
Step-by-step explanation:
The top part equals 1 because anything to the power of zero equals one. then for the second one bring every variable with a negative exponent to the top and leave the 2 at the bottom
To find the x-intercepts algebraically, we let y = 0 y=0 y=0 in the equation and then solve for values of x. In the same manner, to find for y-intercepts algebraically, we let x = 0 x=0 x=0 in the equation and then solve for y.